Sistema de Información para Proyectos de Telemedicina - Aparicio, Lilia E; Coronado S, Paulo C (Revista Científica, 2006)
This article shows a general vision of the research and development of an Information System for Telemedicine and E-health Management Projects in Colombia. In the first place the research has been made in all public hospitals in Bogotá. The work was developed with the aim of identify the main problems that there are around the information systems and interchange services between hospitals and Communications Companies in order to give an effective support to Telemedine Projects. The platform of communications foreseen for the development is offered by the Company of Telecommunications of Bogotá, ETB; the application was released as free software. The first solution includes six subsystems: Health entities, telecommunications operators, interaction between technologies, medical services, equipment and technology, projects and organizations, where is very important the electronic data interchange to give integration of services and the convergence of networks like development tools for the solution of problems of social impact.